Enhancement of mechanical properties of polymeric nanofibers by controlling crystallization behavior using a simple freezing/thawing process. Issue 69 (11th September 2017) - Lee, Hoik; Yamaguchi, Kyohei; Nagaishi, Tomoki; Murai, Masaaki; Kim, Myungwoong; Wei, Kai; Zhang, Ke-Qin; Kim, Ick Soo
Abstract : We demonstrate the modulation of physical and mechanical properties by controlling crystallinity in cross-linked poly(vinyl alcohol) (PVA) nanofibers using a simple and straightforward freezing/thawing process. Abstract : We demonstrate the modulation of physical and mechanical properties by controlling crystallinity in cross-linked poly(vinyl alcohol) (PVA) nanofibers using a simple and straightforward freezing/thawing process. PVA chains in the cross-linked network are swollen and rearrange through the freezing/thawing process, resulting in the formation of more hydrogen bonding and hence, a higher degree of crystallization in the nanofibers compared to pristine electrospun nanofibers. Quantitative analyses with X-ray diffraction and FT-IR studies confirm increases of the crystallite diameter from 24.2 Å to 28.3 Å and the degree of crystallinity from 23.5% to 43.6%, respectively. Also, we found that the increase of crystallinity led to a dramatic enhancement of the mechanical properties: the tensile strength was increased up to ∼165% compared to pristine nanofibers, while the elongation at break was decreased. This straightforward and facile process will enable us to precisely control crystallinity, and also to fine-tune the physical properties of polymeric nanofibers; consequently, the method will broaden the application of polymeric nanofibers.